Data-Based Decision Making by Teachers in K-12 Schools: A Scoping Review - Tayem, Areej; Bourgeois, Isabelle (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2024)
Despite the widespread adoption of data-based decision making (DBDM) policies in schools around the world, there is limited understanding of how teachers use DBDM in K-12 classrooms and the impact of DBDM training on teacher practices and student outcomes. This scoping review aims to provide an overview of the existing literature on the uses of DBDM by teachers globally and identify gaps in the field. The findings (a) highlight a geographical and temporal clustering, with a notable emphasis on studies conducted in the United States and the Netherlands and published in 2016–2017 and 2020–2022; (b) identify a gap in the literature, particularly in the context of online and secondary schools, where the predominant focus has been on elementary and in-person settings; and (c) suggest that although DBDM interventions have been found helpful in altering teacher practices and student outcomes, there is still a need for more sustainable support to enhance DBDM implementation. The study concludes with recommendations for future DBDM research, building on implications from previous interventions.